RELATIONSHIP OF SUICIDE ATTEMPT WITH DEPRESSION AND OTHER SOCIO-DEMOGRAPHIC FACTORS AMONG THE TRANS-GENDERS - Zubair, Usama Bin; Khan, Muhammad Azeem; Jalil, Aneza; Kamal, Asif; Nizami, Asad; Minhas, Fareed; Tasleem, Shumaila (Journal of Ayub Medical College Abbottabad, 2019)
Background: This study was conducted to assess the frequency of suicide attempt among the transgender population and analyse the relationship of depression and other socio-demographic factors with the suicide attempt Cross-sectional study Methods: The sample population comprised of one hundred and forty-eight transgender people of Rawalpindi and Islamabad. Suicidal attempt was assessed by the simple question that Have you ever performed an action with the intent to take your own life in your life time? Answer of yes or no was recorded. Hamilton rating scale for Depression (HAM-D) was used to look for the presence of depression among the target population. Relationship of the age, smoking, family income, illicit substance use and depression was studied with the presence of suicidal attempt among these transgender population of twin cities of Pakistan. Results: A total of 148 transgender people were included in the final analysis. Mean age of the study participants was 38.24±3.18. Out of these, 70.9% had no suicidal attempt in their whole life while 29.1% had one or more suicidal attempts during the course of their life. Twelve had more than one suicidal attempt while 19 had attempt in last one year. Fifty-five did not showed depression while 93 had depression on HAM-D. With binary logistic regression we found that presence of depression and low income had significant association with the presence of suicidal attempt among the target population. Conclusion: This study showed a high prevalence of suicidal attempts among the transgender population of twin cities of Pakistan. Routine screening for mental health problems should be performed on this high-risk group and adequate employment resources should be generated in order to enable them to earn their livelihood and prevent them from making attempts to take their own life. Keywords: depression; suicide attempt; trans-genders